Imaging Modality and Frequency in Surveillance of Stage I Seminoma Testicular Cancer: Results From a Randomized, Phase III, Noninferiority Trial (TRISST). Issue 22 (1st August 2022) - Joffe, Johnathan K.; Cafferty, Fay H.; Murphy, Laura; Rustin, Gordon J.S.; Sohaib, Syed A.; Gabe, Rhian; Stenning, Sally P.; James, Elizabeth; Noor, Dipa; Wade, Simona; Schiavone, Francesca; Swift, Sarah; et al.
Abstract : PURPOSE: Survival in stage I seminoma is almost 100%. Computed tomography (CT) surveillance is an international standard of care, avoiding adjuvant therapy. In this young population, minimizing irradiation is vital. The Trial of Imaging and Surveillance in Seminoma Testis (TRISST) assessed whether magnetic resonance images (MRIs) or a reduced scan schedule could be used without an unacceptable increase in advanced relapses. METHODS: A phase III, noninferiority, factorial trial. Eligible participants had undergone orchiectomy for stage I seminoma with no adjuvant therapy planned. Random assignment was to seven CTs (6, 12, 18, 24, 36, 48, and 60 months); seven MRIs (same schedule); three CTs (6, 18, and 36 months); or three MRIs. The primary outcome was 6-year incidence of Royal Marsden Hospital stage ≥ IIC relapse (> 5 cm), aiming to exclude increases ≥ 5.7% (from 5.7% to 11.4%) with MRI ( v CT) or three scans ( v 7); target N = 660, all contributing to both comparisons. Secondary outcomes include relapse ≥ 3 cm, disease-free survival, and overall survival. Intention-to-treat and per-protocol analyses were performed. RESULTS: Six hundred sixty-nine patients enrolled (35 UK centers, 2008-2014); mean tumor size was 2.9 cm, and 358 (54%) were low risk (< 4 cm, no rete testis invasion). With a median follow-up of 72 months, 82 (12%) relapsed. Stage ≥ IIC relapse was rare (10 events). Although statistically noninferior, more events occurred with three scans (nine, 2.8%) versus seven scans (one, 0.3%): 2.5% absolute increase, 90% CI (1.0 to 4.1). Only 4/9 could have potentially been detected earlier with seven scans. Noninferiority of MRI versus CT was also shown; fewer events occurred with MRI (two [0.6%] v eight [2.6%]), 1.9% decrease (–3.5 to –0.3). Per-protocol analyses confirmed noninferiority. Five-year survival was 99%, with no tumor-related deaths. CONCLUSION: Surveillance is a safe management approach—advanced relapse is rare, salvage treatment successful, and outcomes excellent, regardless of imaging frequency or modality. MRI can be recommended to reduce irradiation; and no adverse impact on long-term outcomes was seen with a reduced schedule.